CRISPR-cas9 Screening Identified Lethal Genes Enriched in Cell Cycle Pathway and of Prognosis Significance in Breast Cancer - Sun, Xi; Wang, Zheng; Chen, Xiaosong; Shen, Kunwei (Frontiers in Cell and Developmental Biology, 2021)
Background: Synthetic-lethal genes have not been systematically analyzed in breast cancer which may have significant prognostic value. The current study aimed to investigate vital genes related to cell viability by analyzing the crispr-cas9 screening data, which may provide novel therapeutic target for patients. Methods: Genes differentially expressed between tumor and normal tissue from the Cancer Genome Atlas (TCGA) and genes related to cell viability by crispr cas9 screening from Depmap were overlapped. GSE21653 set were randomized into training and internal validation dataset at a ratio of 3:1, and external validation was performed in GSE20685 set. The least absolute shrinkage and selection operator (LASSO) regression was used to construct a signature to predict recurrence-free survival (RFS) of breast cancer patients. Univariate and multivariate cox regression were used to evaluate the prognostic value of this signature. Differentially expressed genes (DEGs) between high-risk and low-risk patients were then analyzed to identify the main pathways regulated by this signature. Weighted correlation network analysis (WGCNA) was conducted to recognize modules correlated with high risk. Enrichment analysis was then used to identify pathways regulated by genes shared in the overlapped genes, DEGs, and WGCNA analysis. Results: A total of 86 oncogenes were up-regulated in TCGA database and overlapped with synthetic-lethal genes in Depmap database, which were enriched in cell cycle pathway. A total of 51 genes were included in the gene signature based on LASSO regression. High-risk patients showed worse RFS compared with low-risk patients in internal training, internal validation and external validation dataset. Time dependent receiver operating characteristic curves of 3 year and 5 year indicated that risk score was superior to tumor stage, age, and PAM50 in both entire and external validation dataset. Cell cycle was the main different pathway between the high-risk and low-risk groups. Meanwhile, cell cycle was also the main pathway enriched in the 25 genes which were shared among 86 genes, DEGs, and WGCNA analysis. Conclusion: Cell cycle pathway, identified by crisper cas9 screening, was a key pathway regulating cell viability, which has significant prognostic values and can serve as a new target for breast cancer patient treatment.